Extrahippocampal Desynchronization in Nonlesional Temporal Lobe Epilepsy - Pastor, Jesús (2012)
Although temporal lobe epilepsy (TLE) is traditionally associated with both hypersynchronous activity in the form of interictalepileptic discharges and hippocampal sclerosis, recent findings suggest that desynchronization also plays a central role in thedynamics of this pathology. The objective of this work is to show the imbalance existing between mesial activities in patientssuffering from mesial TLE, with normal mesial structures. Foramen ovale recordings from six patients with mesial TLE and one with lateral TLE were analyzed through a cluster analysis and synchronization matrices. None of the patients present findings in the MRI presurgical evaluation. Numerical analysis was carried out in three different situations: awake and sleep interictal and also during the preictal stage. High levels of desynchronization ipsilateral to the epileptic side were present in mesial TLE patients. Lowlevels of desynchronization were present in the lateral TLE patient during the interictal stage and almost zero in the preictal stage. Implications of these findings in relation with seizure spreading are discussed.